Utilization of Augmented Reality to support the creation of interactive learning media at the Showatul Is'ad Islamic Modern Islamic Boarding School, Pangkep Regency: Pemanfaatan Teknologi AR untuk membuat media pembelajaran Interaktif dan Aplikatif di Pondok Pesantren Modern Islam Shohwatul Is’ad Kabupaten Pangkep. - Mar’atuttahirah, Mar’atuttahirah; Tunnisa, Khaera; Rahman, Rakhmadi; Tri Putra DA, Alvian; Rosmiati, Rosmiati; Abdullah, Abdullah; Barik Alfito, Ramadan; Najwa, Hafizhah; Tri Aditya, Muh (Politeknik Negeri Jember, 2024)
Information technology continues to develop rapidly and can be used to make human work more accessible. In the world of education, students are expected to be able to adapt to the environment and create positive things using technology. Technology can be used in the world of education to support the development of student knowledge. Learning media is one of the factors that play an essential role in the teaching and learning process and knowledge development. The learning media used by the Showatul Is'Ad Islamic Boarding School teachers is textbooks that contain theories that cause students to get bored and not understand abstract material. Therefore, in the research, training was carried out in creating interactive and applicable learning media using the Assemblr Edu Augmented Reality Platform. Developing learning materials using AR can help students easily understand abstract theories by providing virtual, 3D materials and implementing them in the real world. The result of this activity is that the teacher has created learning media material for science subjects that explains body organs, making it easier for students to understand the actual representation of organs and their functions in 3D visual form.